Pemberdayaan Remaja Dalam Pencegahan Faktor Resiko Stunting Sejak Dini - Ni Ketut Ayu Mirayanti; Putra Pradnyantara, I Gusti Agung Ngurah; Ni Luh Nova Dilisca; Wahyu Aditya, Made; Cahya Sari, Lia (Permata Indonesia, 2025)
Stunting is a chronic nutritional problem that affects physical growth, cognitive development, and the productivity of future generations. Prevention efforts need to be carried out upstream, including among adolescents who will become future parents. This community service program aimed to empower adolescents in preventing stunting risk factors through knowledge enhancement, nutrition education, and health screening. The program was implemented at Bali Dewata Health Vocational School in June 2025, involving five lecturers and two students from STIKES Wira Medika Bali. The activities included coordination with the school and primary health center, pretest, health education sessions, health screening (blood pressure measurement and medical history), distribution of educational booklets, and a posttest to evaluate knowledge improvement. A total of 61 students participated in the program. The results showed a significant increase in knowledge about stunting prevention, with the proportion of students in the “good” category rising from 50.8% to 88.5%. Health screening also revealed a small number of students with anemia, a condition that may contribute to future stunting in their offspring. This program highlights the crucial role of adolescents as agents of change in stunting prevention through healthy lifestyles, balanced nutrition, and peer education. With the active involvement of schools, health centers, and students, the program successfully improved adolescent awareness of stunting issues and produced outputs in the form of scientific publication and educational media. Continuous monitoring is planned to ensure program sustainability.